Copy numbers of mitochondrial genes change during melon leaf development and are lower than the numbers of mitochondria - Shen, Jia (Hortic Res, 2019)
Melon is a useful plant species for studying mitochondrial genetics because it contains one of the largest and structurally diverse mitochondrial genomes among all plant species and undergoes paternal transmission of mitochondria. We used droplet digital (dd) PCR in combination with flow cytometric determination of nuclear DNA quantities to determine the absolute per-cell copy numbers of four mitochondrial genes (nad9, rps1, matR, and atp6) across four stages of melon leaf development. The copy numbers of these mitochondrial genes not only varied during leaf development but also differed among each other, and there was no correlation between the copy numbers of the mitochondrial genes and their transcript levels. The gene copy numbers varied from approximately 36.8 ± 4.5 (atp6 copies in the 15th leaf) to approximately 82.9 ± 5.7 (nad9 copies in the 9th leaf), while the mean number of mitochondria was approximately 416.6 ± 182.7 in the 15th leaf and 459.1 ± 228.2 in the 9th leaf. These observations indicate that the leaf cells of melon do not contain sufficient copies of mitochondrial genes to ensure that every mitochondrion possesses the entire mitochondrial genome. Given this cytological evidence, our results indicate that mtDNA in melon exists as a sub-genomic molecule rather than as a single-master circle and that the copy numbers of individual mitochondrial genes may vary greatly. An improved understanding of the molecular mechanism(s) controlling the relative prevalence and transmission of sub-genomic mtDNA molecules should provide insights into the continuity of the mitochondrial genome across generations.